Ordering Information System Design Weddings Organizer Putri Minang uses YII2 Framework - Maulana Putra, Risky; Hendriyani, Yeka (Dinasti Information and Technology, 2023)
Wedding Organizer is services that work in a manner personal For help candidate bride in planning And supervision implementation party wedding in accordance timetable And budget that has set . Objective study This is produce design For build application web- based that provides service related booking at the Princess Wedding Organizer Minang does the ordering process product during This done Still the manual way then need built system information in a manner hurry And more easy . Where system information this is made use use Object Oriented Programming (OOP) concepts and use Unified Modeling Language (UML) modeling . Frameworks used is Yii2 with Language mainly PHP and Java Script. Analysis observation system walk covers a number business processes and data against service booking . Testing to results developed design _ showing that application can used as where should , be proper service _ complete application _ And capable help with the ordering process product.